2013
DOI: 10.1177/0963721413491570
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Health Risks With Visual Aids

Abstract: Informed decision making requires that people understand health risks. Unfortunately, many people are not risk literate and are biased by common risk communication practices. In this article, we review a collection of studies investigating the benefits of visual aids for communicating health risks to diverse vulnerable people (e.g., varying in abilities, ages, risk characteristics, and cultural backgrounds). These studies show that appropriately designed visual aids are often highly effective, transparent, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 235 publications
(162 citation statements)
references
References 53 publications
9
147
1
5
Order By: Relevance
“…This is an impressive finding, since the stress of using a less proficient language could have diminished the cognitive resources needed for deliberative reasoning, thus pushing people to make gut, instinctive, or emotional responses. Note that framing effects are reduced or eliminated when problems are depicted using graphical aids, confirming the role of language (Garcia-Retamero & Cokely, 2013). Similar findings were obtained using a loss-aversion paradigm.…”
Section: Decision Making In a Foreign Languagesupporting
confidence: 78%
“…This is an impressive finding, since the stress of using a less proficient language could have diminished the cognitive resources needed for deliberative reasoning, thus pushing people to make gut, instinctive, or emotional responses. Note that framing effects are reduced or eliminated when problems are depicted using graphical aids, confirming the role of language (Garcia-Retamero & Cokely, 2013). Similar findings were obtained using a loss-aversion paradigm.…”
Section: Decision Making In a Foreign Languagesupporting
confidence: 78%
“…Educational materials should include visuals aids (e.g., pie charts, icon arrays) and be targeted at appropriate reading levels for youth and parents of varied educational levels. Such an approach has been shown to make materials more accessible for individuals with low health literacy levels due to age, language, and limited medical knowledge [16]. For example, a systematic review of interventions for individuals with low health literacy found several effective design features to mitigate the effects of low health literacy such as including icon arrays to numerical information, adding video to verbal narrative, presenting information so that the higher number is better, and presenting important information first or by itself [17].…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, many studies have examined the effects of visual aids (for reviews, see Ancker et al, 2006;Garcia-Retamero and Cokely, 2013;Garcia-Retamero et al, 2012;Lipkus, 2007;Lipkus and Hollands, 1999). These studies have shown that although people are not generally good at understanding probability information, their understanding is improved with visual aids.…”
Section: Risk Judgments and Visual Aidsmentioning
confidence: 99%